Chemical analysis of industrial water - McCoy, James W. (Chemical Pub. Co., 1969)
Annotation This classic book has been reprinted by popular demand. Analytical chemists and chemical engineers will find this a well written and well illustrated treatise dealing with (and finding solutions to) the problems of water treatment, plant corrosion, and chemical analysis connected with the chemical process industries, steam and power plants and petroleum refining. This is an excellent manual for both laboratory and field workers.
Keywords: Industrial water supply.; Water -- Analysis.; Feed-water purification.; Steam-boilers -- Incrustations.; elektronické knihy; electronic books